Influence of Thai street food quality, price, and involvement on traveler behavioral intention: exploring cultural difference (Eastern versus Western) - Jeaheng, Yoksamon; Al-Ansi, Amr; Chua, Bee-Lia; Ngah, Abdul Hafaz; Ryu, Hyungseo Bobby; Ariza-Montes, Antonio; Han, Heesup (Dove Medical Press, 2023)
Introduction: Gastronomy tourism has become a phenomenal trend of the global tourism industry in the 21st century. As the tourism industry and its related foodservice businesses flourish, street food has received increasing popularity with its combination of local delights and the cultural value of the destination. This study examined the psychology of street food consumption and assessed the effect of street food quality that is represented by the cultural experience, health and safety of the food, food sensory appeal, staff service, physical environment, the meal menus with perceived reasonable prices, involvement in Thai street food, and repurchase intention from an international tourist perspective. Methods: A survey method along with a quantitative structural analysis was used. Results: The findings revealed that Thai street food quality positively and significantly predicted the international tourists’ perceived reasonable prices, involvement, and repurchase decisions. Perceived reasonable prices and involvement were found to be important mediators between Thai street food quality and repurchase intentions. Moreover, this research identified the significant moderating role of Eastern and Western cultures.